Federalising religious courts in Malaysia: lessons from the Indonesian peradilan agama - Shuaib, Farid Sufian; Nik Yahya, Nik Mohd Fitri (2014)
Religion has an important place in the state and governance in Malaysia. The basic document of the state, namely the Federal Constitution, provides that Islam as the religion of the Federation and allows for the setting up of religious courts. As a federation consisting of thirteen states and the federal territories, Malaysia has fourteen courts of final appeals for its religious courts – known as Syariah courts in Malaysia. This comes about since religious courts are under the respective states and federal territories’ powers. As a unitary state, it is possible for Indonesia to provide a comparative framework for Malaysia to learn in its quest to harmonise religious courts. The structural framework of the judicial system in Indonesia such as the relationship between the religious courts (peradilan agama) and general courts (peradilan umum) could be compared with the Syariah courts and the civil court in Malaysia. Furthermore, the singular reference to the Indonesian Supreme Court of cases from different provinces smoothen harmonisation of various courts’ decisions.